Marine anaerobic bacterial diversity for the production of antimicrobial agents - K Muddukrishnaiah; V P Shilpa (Wolters Kluwer Medknow Publications, 2017)
Background: Bacterial resistance to antibiotics has led to a search for new antimicrobial agents. Infectious diseases caused by bacteria, fungi and viruses are a major threat to human health. Materials and Methods: Sixty marine soil samples were collected from different coastal zones and different sampling sites in Kerala and kept for anaerobic enrichment. Enrichment culture was screened for antibacterial activity by crowded plate method. From the sixty marine samples, twenty bacterial strains were isolated. Among the twenty bacterial strains, KS302 showed antimicrobial activity. Further analysis was established in aqueous and organic solvents of the crude extract. These secondary metabolites were studied for antimicrobial activity against clinical isolates of S.aureus (NCIM-5345), B. Subtilis (NCIM-2920), and E. coli (NCIM-5346). Results: Antimicrobial compound producing microorganisms were identified by anaerobic crowded plate method and purified by streak plate method. Methanolic extract as well as lipid layer did not show any antimicrobial activity but solvent layer as well as aqueous layer had shown good antimicrobial activity against all the test organisms like S.aureus (NCIM-5345), B. Subtilis (NCIM-2920), and E. coli (NCIM-5346). Conclusion: Marine anaerobic microorganisms can be explored by isolating a novel compound, which can be used as the drug of choice against pathogenic bacteria.